The problems of the marginalization of border areas using the example of Prudnik District - Korenik, Stanisław; Żurakowski, Artur (Problemy marginalizacji obszarów przygranicznych na przykładzie powiatu prudnickiego, 2018)
Contemporary developmental processes take place in diverse ways in socio-economical space. Diversity occurs among individual regions as well as inside of those regions. The border areas are a specific example of this. As commonly is accepted, they show a natural tendency to peripherality. The reasons for this are manifold and in the contemporary realities of Central Europe, they cannot be attributed only to location. The aim of this article is to systematize the knowledge about border areas and the reasons for their peripherality, and an example of Prudnik District has been used
Biblioteka Regionalisty, 2018, Nr 18, s. 27-38
Keywords: region; border area; peripherality; endogenous resources; obszar przygraniczny; peryferia; zasoby endogeniczne